Development and pilot evaluation of a mobile app on parent-child exercises to improve physical activity and psychosocial outcomes of Hong Kong Chinese children - Rosa Sze Man Wong; Esther Yee Tak Yu; Thomson Wai-Lung Wong; Colman Siu Cheung Fung; Cynthia Sin Yi Choi; Calvin Ka Lun Or; Kiki Sze Nga Liu; Carlos King Ho Wong; Patrick Ip; Cindy Lo Kuen Lam (BMC, 2020)
Abstract Background Parent-child exercises involve children and parents to do workout together and have positive effects on physical and mental health. We developed a mobile app on parent-child exercises called Family Move, which combines coaching videos with game features such as points and level system to enhance the health and wellbeing of both children and parents through parent-child exercises. This pilot pre-post study investigated whether the Family Move app-based intervention had a positive effect on children's health-related quality of life (HRQOL), psychosocial wellbeing, and physical activity (PA) level. Methods We recruited 67 parent-child pairs. During the 8-week intervention, these pairs were invited to perform parent-child exercises using the Family Move app. Points were automatically added to the user account after viewing a coaching video. In-game ranking was available to enhance user engagement. Parent proxy-report questionnaires on children's HRQOL, psychosocial wellbeing, and PA were administered at baseline and 1- and 6-month follow-up. Paired samples t-tests were conducted to evaluate post-intervention changes in child outcomes (HRQOL, psychosocial wellbeing, and PA). Multiple linear regressions were used to examine these changes as a function of in-game ranking. Results 52 (78%) viewed at least one coaching video in the Family Move app. Children's PA level significantly increased at 1-month (d = 0.32, p = 0.030) and 6-month (d = 0.30, p = 0.042) follow-up, whereas their psychosocial problems declined at 6-month follow-up (d = 0.35, p = 0.005). Higher in-game ranking was significantly associated with fewer psychosocial problems at 1-month follow-up (β = − 0.15, p = 0.030). Conclusions Our findings suggest that the Family Move app could be a possible intervention to increase children's PA level and psychosocial wellbeing through parent-child exercise. Trial registration ClinicalTrials.gov number, NCT03279354 , registered September 11, 2017 (Prospectively registered).